2004
DOI: 10.1007/s10595-005-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical activation of aluminum: 2. Size, shape, and structure of particles

Abstract: The structure of active Al/C composite prepared by the mechanochemical method from aluminum and graphite powders (10-30 wt % C) is studied by scanning and transmission electron microscopies, atomic force microscopy, local elemental analysis, X-ray diffraction, as well as by adsorption and sedimentation measurements. It is established that the particles of chemically active Al/C composite represent porous plate-like aggregates with a mean size smaller than 2.5-5 µ m and composed of nanocrystalline aluminum bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
(12 reference statements)
0
6
0
Order By: Relevance
“…The preparation procedure for such composite and its structure are described in previous papers [3,4]. The particles of Al + (10-30 wt %) C composite powder consist of nanocrystalline blocks of aluminum distributed in the matrix of amorphous carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation procedure for such composite and its structure are described in previous papers [3,4]. The particles of Al + (10-30 wt %) C composite powder consist of nanocrystalline blocks of aluminum distributed in the matrix of amorphous carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The fact of the aluminum grinding is confirmed by the data of electron and atomic force microscopies (see next communication [16]). The graphite crystals are more sensitive to mechanical loading than aluminum and the grinding of graphite makes a major contribution to the value of specific surface area (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…% and demonstrated that, after the treatment in an energy-intensity planetary mill for 40-200 h (we estimated the absorbed energy dose as 150-700 kJ/g), the product nature is determined by the Al/C ratio in the initial mixture. At low carbon content (16)(17)(18)(19)(20)(21)(22)(23) at. %), the mechanochemical treatment results first in the formation of carbide which finally (after 220 h!)…”
Section: Introductionmentioning
confidence: 99%
“…The mixture was milled for 1 h at 20 Hz frequency, similar to the experiment performed by Streletskii et al [8]. For the mixture, high purity carbon in he form of spectral coal (Ringsdorff, Germany) as used for the preparation of electrodes for dc-ark spectrometry was used.…”
Section: Methodsmentioning
confidence: 99%